Optimal pressure sensor locations in smart insoles for heel-strike and toe-off detection - Chen, Diliang; Ghoreishi, Nozhan; Olugbon, Femi; Ansah, Stella; Huang, Ming-Chun; Yu, Qiaoyan (2022 IEEE Biomedical Circuits and Systems Conference (BioCAS), 2022)
Heel-strike and toe-off are important gait events for gait analysis. Smart insoles with pressure sensors in different locations have been proposed to detect these two gait events. However, there is no research to reveal optimal sensor locations under the foot for heel-strike and toe-off detection. To address this problem, a novel method based on the mechanism of heel-strike and toe-off detection was proposed to find out the optimal sensor locations. A smart insole system, which has 96 pressure sensors uniformly distributed on it, was used to supply ground truth. Experiment data was collected from six subjects, each of whom wore a pair of smart insoles and walked 15 steps at their comfort speeds. The results showed that two top optimal pressure locations identified with the proposed method were enough to detect heel-strike and toe-off with good accuracy. Options of top optimal sensor locations for heel-strike and toe-off detection were mainly concentrated in the middle of the heel area (sensors 5, 6, 8, 10, 11, 13, and 14) and the front edge of the metatarsal bone area (sensors 55, 59, 60, and 61), respectively. This research provided references for future researchers to effectively use pressure sensors for smart insole design and gait analysis.